2014
DOI: 10.3109/00952990.2014.940424
|View full text |Cite
|
Sign up to set email alerts
|

Prescription opioid misuse and mental health among young injection drug users

Abstract: Background Prescription opioid (PO) misuse is a significant concern in the United States. Objectives This study describes the prevalence and timing of PO misuse, diagnoses of opiate abuse and dependence, and their associations with psychiatric disorders in a sample of young people who inject drugs (PWID). Methods Participants were 570 young (18–25 years) PWID, primarily heroin users, recruited through outreach and respondent-driven sampling. Trained interviewers administered a semi-structured psychiatric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…Differences between groups also existed prominently when examining the mental health of respondents. Previous studies have identified a number of relationships between mental health disorders and prescription opioid use including bipolar disorder, post‐traumatic stress disorder (PTSD), panic and depressive symptoms . In addition to supporting these existing data, this study provides a more nuanced look at this relationship: current prescription opioid medication misusers were more likely than past misusers, who were more likely than non‐misusers, to report more depressive symptoms (as measured by the PHQ‐9), to screen positive for PTSD, to endorse more symptoms of anxiety, to screen positive for ADHD, and to be either currently taking prescribed mental health medications or to have been treated for psychological/emotional problems in the past.…”
Section: Conclusion and Scientific Significancesupporting
confidence: 58%
“…Differences between groups also existed prominently when examining the mental health of respondents. Previous studies have identified a number of relationships between mental health disorders and prescription opioid use including bipolar disorder, post‐traumatic stress disorder (PTSD), panic and depressive symptoms . In addition to supporting these existing data, this study provides a more nuanced look at this relationship: current prescription opioid medication misusers were more likely than past misusers, who were more likely than non‐misusers, to report more depressive symptoms (as measured by the PHQ‐9), to screen positive for PTSD, to endorse more symptoms of anxiety, to screen positive for ADHD, and to be either currently taking prescribed mental health medications or to have been treated for psychological/emotional problems in the past.…”
Section: Conclusion and Scientific Significancesupporting
confidence: 58%
“…Primarily, in this study, the central theme that emerged was that polydrug abuse is predominantly associated with Twitter prescription drug abuse discussions and could be indicative of larger behavioral trends of users abusing multiple prescription drugs and also combining use with other illicit substances. These results could form the basis for future indepth studies examining the unique health and substance abuse consequences associated highly prevalent polydrug uses (including potentially linkages to mental health issues and behavior among young adults and adolescents already identified in the literature) (Fink et al, 2015;Kelly, Wells, Pawson, LeClair, & Parsons, 2014;Mackesy-Amiti, Donenberg, Ouellet, 2015).…”
Section: Resultsmentioning
confidence: 80%
“…This link is unsurprising given the literature documenting multiple mental health problems associated with prescription opioid misuse, including among young adult injection drug users (Mackesy-Amiti, Donenberg, and Ouellet 2015). However, mental health problems are also associated with HIV transmission risk among substance users (German and Latkin 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The misuse of prescription opioids among young people is associated with several health and social problems, including mental distress, victimization, and homelessness (Schrager et al 2014, Mackesy-Amiti, Donenberg, and Ouellet 2015, Jessell et al 2015). The use of alternate routes of administration of prescription opioids, including snorting, smoking, or injecting, may result in increased vulnerability, as the effects of the drug are intensified and the risk of addiction is elevated (Compton and Volkow 2006).…”
mentioning
confidence: 99%